2022
DOI: 10.1155/2022/8437066
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in Retinal Vessel Flow after Small Incision Lenticule Extraction

Abstract: Objective. In order to analyze changes in retinal vessel flow after small incision lenticule extraction (SMILE). Methods. A total of 32 patients (62 eyes) who underwent SMILE were enrolled in this prospective study. Optical parameters, including vessel density (VD), and perfusion density (PD) of foveal, parafoveal, and perifoveal regions, respectively, were measured before surgery and at 1 day, 1 week, 1 month, and 3 months postoperation. Preoperative parameters and surgical parameters were recorded. Results. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%